Struktur Kurikulum dan Pengembangan Kompetensi Numerasi: Analisis Komparatif Pendidikan Matematika di Indonesia dan Finlandia - Muhammad Ilham Wahyudi; Itun Delima Mira; Megawati Megawati; Muji Rahayu; Nurhasdira Nurhasdira; Nurvita Sugiarti; Rosa Rachmat; Yulina Eva Riany (De Fermat : Jurnal Pendidikan Matematika, 2026)
Numeracy competence is a fundamental skill that determines students' readiness to meet twenty-first century demands. Persistent cross-national gaps in achievement, most recently documented in PISA 2022, suggest that differences in curriculum design play a substantial role in shaping those disparities. This study examined the relationship between mathematics curriculum structure and the development of numeracy competence through a comparative analysis of Indonesia and Finland. A Systematic Literature Review (SLR) guided by the PRISMA 2020 framework was conducted across Google Scholar, Scopus, and SINTA databases using Publish or Perish, producing 15 articles from an initial pool of 130 based on predetermined inclusion criteria and quality appraisal using an instrument adapted from the Critical Appraisal Skills Programme (CASP). Thematic analysis suggests that Finland's coherent, conceptually oriented curriculum appears to be associated with the development of students' reasoning and problem-solving abilities, whereas Indonesia's curriculum, which remains comparatively fragmented and procedurally focused, appears to constrain the development of contextual numeracy. The results indicate that curriculum effectiveness in supporting numeracy is determined not merely by written content, but by the extent to which curriculum structure shapes students' overall learning experiences. The implications of this study are relevant to curriculum policy and mathematics curriculum design in Indonesia.